Pengembangan Media Cerita Bergambar pada Pembelajaran IPS untuk Meningkatkan Minat Belajar Siswa Kelas IV SDN Inpres Rabakodo - Naufal Fadlan; A. Gafar Hidayat; Ratnah Ratnah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to develop illustrated story media to increase interest in learning social studies subjects for grade IV students of SDN Inpres Rabakodo. This study uses the R&D method, to develop illustrated story media as a learning media for social studies for grade IV elementary school students. By using the Borg and Gall model which includes 5 stages, namely potential and problems, collecting data, product design, product validation, and design revision. The results of the study showed that the validity of the illustrated story media from 4 media and material validators obtained an average score of 83.26 categorized as very feasible. The questionnaire response of limited test students showed the practicality of the illustrated story media with an average score of 85.16 categorized as very practical. The results of the development of illustrated story media carried out by measuring student learning interest were 82%, compared to before the use of the story media, student learning interest was only 45%. This means that the results of the development can significantly increase student learning interest